Relation of Premium Collection and Investment Pattern of Non-Life Insurance Company - Yadav, Mukesh Kumar (KMC Research Journal, 2024)
Insurance is a contract where the policyholder receives financial compensation for specific risks or events. The main objective of this study was to evaluate the relationship between Shikhar Insurance Company and Neco Insurance Company by analyzing their premium collection and investment patterns. Data from the past five years was gathered, and relevant information was selected for the study. The data was organized systematically before applying financial and statistical tools for analysis. The analysis focused on trends and correlation, revealing that both companies saw an increase in premium collection and investments from FY 2017/2018 to FY 2021/2022. A strong positive correlation was found between premium collection and investment patterns.